Relações entre voluntariado e cidadania à luz das motivações - Caldas, Patrícia Trindade (2020)
As an expanding phenomenon around the world, volunteering has been recognized for its potential for the development of citizenship by promoting opportunities for the realization of active community engagement practices focused on collective well-being. From this perspective, it is the thesis that volunteers are more likely to perform citizen higher than nonvolunteers, stimulated by the motivations that guide their behavior: the closer to selfless motivations, the more volunteers are concerned about collective issues and, consequently, more tend to develop citizenship practices. Thus, the aim of this study is to understand the relationships between voluntary activity and citizenship practices, through the inherent motivation. Methodologically, we opted for the quali-quantitative research, through the use of bibliographic research, semi-structured interviews, surveys with three samples (from 207, 522 and 366 subjects), descriptive and inferential statistics and modeling of structural equations. The main results were: (1) the development of a scale of validated and contextualized citizenship practices at the national level that measure citizenship practices at individual level in four spheres: civil, political, social and environmental; (2) confirmation of the overlapping of citizen performance of volunteers on non-volunteers in all spheres of citizenship practices; and (3) the identification of social justice motivations and altruism as main explanatory forces for the citizen behavior of the volunteers surveyed. Selfish motivations also appeared as drivers of citizen behavior, in the political and social dimensions.